1996
DOI: 10.1042/bj3160551
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of proliferation of LLC-MK2 cells by nucleosides and nucleotides: the role of ecto-enzymes

Abstract: 1. Using the incorporation of [methyl-3H]thymidine as a proliferation marker, the effects of various nucleosides and nucleotides on endothelial LLC-MK2 cells were studied. We found that ATP, ADP, AMP and adenosine in concentrations of 10 microM or higher stimulate the proliferation of these cells. 2. Inhibition of ecto-ATPase (EC 3.6.1.15), 5'-nucleotidase (EC 3.1.3.5) or alkaline phosphatase (EC 3.1.3.1) significantly diminished the stimulatory effect of ATP, indicating that the effect is primarily caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 51 publications
(60 reference statements)
2
10
0
1
Order By: Relevance
“…We have previously shown that DIDS inhibits T. cruzi epimastigote cell growth (Bernardes et al 2000), and that this inhibition is supposed to be related to ectoenzymes involved in cell proliferation (Berreˆdo-Pinho et al 2001). ATP and other nucleotides stimulate the proliferation of different cell types, while the inhibition of the ecto-ATPase, 5¢ nucleotidase and alkaline phosphatase moderate the stimulatory effect of ATP (Lemmens et al 1996). Figure 4 shows that the Mg 2+ -dependent ATPase activity decreased during the time course of cell growth.…”
Section: Resultsmentioning
confidence: 91%
“…We have previously shown that DIDS inhibits T. cruzi epimastigote cell growth (Bernardes et al 2000), and that this inhibition is supposed to be related to ectoenzymes involved in cell proliferation (Berreˆdo-Pinho et al 2001). ATP and other nucleotides stimulate the proliferation of different cell types, while the inhibition of the ecto-ATPase, 5¢ nucleotidase and alkaline phosphatase moderate the stimulatory effect of ATP (Lemmens et al 1996). Figure 4 shows that the Mg 2+ -dependent ATPase activity decreased during the time course of cell growth.…”
Section: Resultsmentioning
confidence: 91%
“…The physiological role of the ecto-ATPases is still unknown, but a possible involvement in cell proliferation has been proposed (Lemmens et al 1996;Bernardes et al 2000;Berreˆdo-Pinho et al 2001). The trypanosomatidae family includes species that cannot synthesize purines de novo and thus are dependent on exogenous sources of these essential nutrients (Cohn and Gottlieb 1997;Gero 1998).…”
Section: Resultsmentioning
confidence: 99%
“…30,31 In comparison with ATP or uridine 5Ј-triphosphate, 5Ј-mononucleotides usually have much lower agonist activity for the nucleotide receptors. 32,33 However, it has been found that AMPS is a weak agonist of a novel P2 receptor on undifferentiated HL-60 cells. Its pharmacological profile is very similar to that of the P2Y11 receptor identified in 2 different cell lines: the 1321N1 astrocytoma and the Chinese hamster over K1 cell line.…”
Section: Discussionmentioning
confidence: 99%